Acetate Production by Moorella thermoacetica via Syngas Fermentation: Effect of Yeast Extract and Syngas Composition - Budi Mandra Harahap; Birgitte K. Ahring (Fermentation, 2023)
Gasifiers produce a gaseous mixture of CO/CO2/H2, also known as synthesis gas (syngas), containing varying compositions and ratios depending on the lignocellulose material types, gasifier design, and gasification conditions. Different physicochemical and thermodynamic properties of each gas type in the various syngas blends can influence syngas fermentation performance for the production of chemicals such as acetate. This study examined the effect of syngas composition (CO, CO/H2, CO/CO2/H2, and CO/H2) and its corresponding ratio on acetate production using Moorella thermoacetica, a thermophilic homoacetogen as the biocatalyst. We also investigated the effect of yeast extract addition for enhancing acetate production. A syngas fermentation study performed at a total pressure of 19 psig (2.29 atm) demonstrated that syngas fermentation in the absence of CO (30%CO2/70%H2) or at low CO proportions (21%CO/24%CO2/55%H2) resulted in the highest volumetric productivity of acetate (0.046 ± 0.001 and 0.037 ± 0.001 g/L/h, respectively). Interestingly, syngas fermentation without CO reached the highest YP/X of 22.461 ± 0.574 g-acetate/g-biomass, indicating that more acetate was produced compared to cell biomass. Higher biomass production was obtained when the CO proportion was increased up to 75% in CO/H2 fermentation. However, the cell growth and acetate production dramatically decreased with increasing CO proportion up to 99.5% CO as the sole constituent of the syngas. Even so, acetate production using 99.5% CO could be improved by adding 2 g/L yeast extract.